Estacionalidad Reproductiva de la Hembra Bufalina (Bubalus bubalis) - Sánchez, Jorge Alberto (2017)
The aim of this study was to describe the reproductive seasonality in buffalo under tropical conditions in the Middle Magdalena, Colombia and its relation to climate parameters. Birth records of 30 571 animals from 1970 to 2013 and hydro-meteorological data from Puerto Berrio-Antioquia station were evaluated. For the analysis a Poisson regression and Spearman correlation was used to determine the relationship between the season of conception and births (expressed in percentage) with the following hydrometeorological variables: minimum, average and maximum monthly flow of rivers (m3/sec), mean values, maximum monthly river levels (cm), monthly total values of sunshine (oC), minimum, average and maximum monthly temperature (oC), mean monthly values of relative humidity (%), monthly maximum values of precipitation (mm in 24 h), monthly totals of precipitation (mm) and the temperature and humidity index (THI). Conception rate was higher during the first quarter of the year and the increased likelihood of births occurred during the second half. There was a negative correlation (p<0.05) between conception and the maximum monthly values of river flows, minimum monthly average values of temperature and monthly minimum temperature values. Also, a positive correlation with the monthly average values of relative humidity and maximum monthly precipitation values. There was a negative relationship between ITH with births and conceptions. The results showed that the buffalo in Colombia has estrous cycles throughout the year, with a seasonality related with temperature, rainfall and relative humidity.